Potential of native sago starch as prebiotic with an anti-obesity functionality - Thompson Laang, Mayrilyn Solo (2018)
One hypothesis that has gained attention for the occurrence of obesity is due to the reaction of the microorganisms in our gut. It have been established that the food intake and dietary composition modulates the composition of the gut microbiota. Resistant starch has gained attention due to its benefits to host‘s health which resembles prebiotics. Sago starch has been reported containing 69% of RS. Sago starch is an important agricultural commodity in Sarawak; however, it is less exploited. This study aimed to determine the potential of sago starch as prebiotics and evaluating the range of low dosage that can confers health benefit in obese management which could be added as functional value to increase its competitiveness with other starches. A 48 male Sprague Dawley rats were fatinduced for 6 weeks prior to RS intervention. Resistant starch intervention was conducted for 8 weeks. Body weight and food intake were observed every week. Faecal samples were collected every 2 weeks interval. At the end of treatment, the rats were sacrificed and gastrointestinal tract were extracted for further analysis. Faecal sample subjected to bacteria profiling using the fluorescent in-situ hybridisation (FISH) technique. Both faecal and caecum sample were subjected to short chain fatty acids analysis using high-performance liquid chromatography. Hepatic lipid content were measured using Folch method. All dosage of sago starch showed a strong correlation of body weight loss, with reduction of food intake. This pattern suggests satiety properties. The increment of dosage RS in treatment showed an increment of Bifidobacterium spp. and Lactobacillus spp. regardless of phenotype when compared to 0% RS group. This pattern suggests the sago starch having bifidogenic factor. Short chain fatty acids analysis conducted in the faecal and caecum samples showed demonstrated a significant increase of the total SCFA production. Acetate, propionate and butyrate concentration are higher in sago starch group when compared to 0% RS group in both ceacum and faecal sample. Hepatic lipid analysis demonstrated sago starch group (4% SRS, 8% SRS, and 16% SRS) have lower fats accumulation in liver when compared to Hi-maize. Body fats tissues also showed that RS-enriched diets group have lower fats than the low-fat diet and 0% RS group. The overall results show that sago starch elicits the similar effect as Hi-maize that can bring benefits to health. Sago starch at low dosage has the potential as a prebiotics with anti-obesity functionality with a consistent consumption.